Imagining grim stories to reduce redundant deliberation in critical incident decision-making. Issue 1 (2nd January 2022) - Alison, Laurence; Shortland, Neil; Palasinski, Marek; Humann, Michael
IMPACT: Leaders spend years developing their abilities and acquiring expertise in their specialist fields, in order to become competent and skilled decision-makers. These capabilities are tested during critical incidents—especially in situations where there is no official guidance or where experience is lacking (because of the rarity of such events). Training at this level needs to facilitate creativity, problem-solving, feedback, self-reflection, and hindsight knowledge, building a pool of uncertainty management skills to fall back on when faced with unprecedented situations beyond the scope of protocol (or current expertise).